Education About the Provision of Supplementary Feeding to Toddler Mothers - Sriwiyanti; Hartati, Sri; Eliza (Chakra Brahmanda Lentera Institute, 2023)
Background: The most important phase in growth and development is infancy and toddlerhood because that is the most important time for parents to build a foundation for growth and development of their children. Nutrition is the most important part in the growth and development of toddlers which is closely related to health and intelligence. the purpose of this research is to know education about the provision of supplementary feeding to toddler mothers. Methods: Design of this research is quantitative with the Quasy Experimental One Group Pretest Posttest design. Giving education to mothers who have toddlers about how to provide supplementary food (PMT) for toddlers using booklets. Comparing the level of knowledge before and after being given education. Subjects were all toddler mothers in Perigi Village, Pulau Pinang District, Lahat District, totaling 75 people. The sampling technique was total sampling. Bivariate analysis was carried out by statistical tests using the Paired Samples T test. Results: showed that there was a significant difference, after counseling with booklet media on increasing knowledge about Supplemental Feeding (PMT) for mothers under five in Perigi village. The level of good knowledge before the intervention was 6 people (8%) and the level of good knowledge increased to 35 people (46.8%). The use of Booklet media is proven to increase the level of knowledge. Booklets are made attractively so that mothers can easily study at home independently. Conclusion: The benefits increasing the knowledge of toddler mothers about supplementary feeding (PMT) for toddlers. With increased knowledge about supplementary feeding (PMT), it is hoped that mothers can change their behavior in preparing food for toddlers.